Advances in the treatment of intrahepatic cholangiocarcinoma: An overview of the current and future therapeutic landscape for clinicians. (19th October 2022) - Moris, Dimitrios; Palta, Manisha; Kim, Charles; Allen, Peter J.; Morse, Michael A.; Lidsky, Michael E.
Abstract: Intrahepatic cholangiocarcinoma (ICC) is the second most common primary liver tumor and remains a fatal malignancy in the majority of patients. Approximately 20%–30% of patients are eligible for resection, which is considered the only potentially curative treatment; and, after resection, a median survival of 53 months has been reported when sequenced with adjuvant capecitabine. For the 70%–80% of patients who present with locally unresectable or distant metastatic disease, systemic therapy may delay progression, but survival remains limited to approximately 1 year. For the past decade, doublet chemotherapy with gemcitabine and cisplatin has been considered the most effective first‐line regimen, but results from the recent use of triplet regimens and even immunotherapy may shift the paradigm. More effective treatment strategies, including those that combine systemic therapy with locoregional therapies like radioembolization or hepatic artery infusion, have also been developed. Molecular therapies, including those that target fibroblast growth factor receptor and isocitrate dehydrogenase, have recently received US Food and Drug Administration approval for a defined role as second‐line treatment for up to 40% of patients harboring these actionable genomic alterations, and whether they should be considered in the first‐line setting is under investigation. Furthermore, as the oncology field seeks to expand indications for immunotherapy, recent data demonstrated that combining durvalumab with standard cytotoxic therapy improved survival in patients with ICC. This review focuses on the current and future strategies for ICC treatment, including a summary of the primary literature for each treatment modality and an algorithm that can be used to drive a personalized and multidisciplinary approach for patients with this challenging malignancy.